In vitro growth and development of Dendrobium hybrid orchid - Khatun, H; Khatun, MM; Biswas, MS; Kabir, MR; Al-Amin, M (Bangladesh Journal of Agricultural Research, 2010)
The experiment was conducted to investigate the combined effect of different plant growth regulators and charcoal supplementation in MS medium on growth and development of plantlets regenerated from protocorm like bodies (PLBs) of hybrid orchid. The combination of BAP + NAA, BAP + IAA, BAP + IBA, and IAA + IBA at different concentrations with charcoal supplementation was studied. The result revealed that the use of different growth regulators had significant effect on different parameters studied. The maximum weight of PLBs (5.123 g) was obtained from the combination of BAP + IBA at 1.0 mg/l each. The highest shoot height (3.239 cm) and maximum number of rooted plantlets (4.473) was obtained from 1.0 mg/l each of BAP + NAA combination. The maximum number of leaves (3.490) and the maximum length of leaves (1.946 cm) were obtained from 1.0 mg/l each of BAP + IBA and the highest leaf width (1.166 cm) was obtained from 0.5 mg/l BAP +1.0 mg/l IBA combination. The highest root length was obtained from 0.5 mg/l each of BAP + IAA and the maximum number of regenerated plantlets (20) was obtained from 0.5 mg/l IAA + 1.0 mg/l IBA combination. However, the maximum fresh weight of single shoot (0.219 g) and the maximum number of roots per plantlet (6.300) was obtained from 1.0 mg/I each of IAA + IBA combination. Keywords: Dedrobium; orchid; hybrid; In vitro growth. DOI: 10.3329/bjar.v35i3.6457 Bangladesh J. Agril. Res. 35(3) : 507-514